Strategies Used By Subtitler In Dark Shadows Movie (2012) - Cahyaningtyas, Ika, Drs. Dwi Haryanti, M.Hum, Drs. Sigit Haryanto, M.Hum (2013)
This research studies about strategies used by subtitler in Dark Shadows movie. The objectives of the study are to explain the types of subtitle strategy use in its subtitle. This research applies descriptive qualitative research. By applying this method, the researcher uses the subtitle of Dark Shadows movie as the data source, while the data of the research are subtitle strategy. As the comparison, there are also data taken from manuscript in English and Indonesian. The method of collecting data is document, reading the original and the subtitling of the movie. The technique of analysis applied in this study is descriptive analysis. The result of the research shows that there are 805 data of subtitling. From 805 data of subtilting, the researcher finds uses of subtitle strategy: 1) expasion, 2) paraphare, 3) transfer, (4) imitation, (5) transcription, (6) dislocation, (7) condensation, (8) decimation, (9) deletion, (10) resignation. In subtitling analysis, the researcher finds 9 data or 1,1% belong to expasion strategy, 100 data or 12,4% belong to paraphrase, 401 data or 49,3% belong to transfer, 176 data or 21,9% belong to imitation, 25 data or 3,1% belong to transcription, haven't data belong to dislocation, 57 data or 7,1% belong to condensation, 7 data or 0,9% belong to decimation, haven't data belong to deletion, 30 data or 3,7% belong to resignation.